How to teleconference effectively. (25th September 2015) - Williams, H.C.; Chalmers, J.R.
Summary: Teleconferencing, whereby a meeting is conducted over the telephone, is a convenient way of getting clinical, management or research business done for people residing in different locations, saving travelling time and costs, and reducing carbon emissions. Despite the convenience, teleconferences are often run poorly, due to inadequate planning or lack of understanding of the technology. Non‐engaged participants typing emails, loud background noises and failure of the chair to bring in all participants and sum up are common problems. This Perspectives article seeks to offer some simple practical guidance to those hosting and participating in teleconferences in order to improve effective communication and efficient decision making.